A PARADIGM SHIFT OF “ASWAJA AN-NAHDLIYYAH” - Kholid Thohiri (IAIN Tulungagung, 2019)
Nahdlatul Ulama (NU) constitutes an important link to the genealogy of Islamic thoughts since inheriting intellectual tradition of classical Muslim scholars. This position delivers a unique approach as to which the NU responds to the changes and reformation of Islamic thoughts. This paper discusses the epistemological position of NU in its relation to the Sunni-theology of Ahlussunnah wa al-Jama‘ah (Aswaja) through examining social relevance and actors-oriented approaches. The article further argues the significance of three cultural fields relevant to better comprehend contemporary dynamics of the NU: namely Pesantrens, Islamic Colleges (PTKI) and Non-Governmental Organizations (NGO). Combining three approaches of Thomas Kuhn’s Shifting Paradigm, Karl Manheim’s Sociology of Knowledge and Abed al-Jabiri’s Epistemology, the article unveils the dynamics of a shifting paradigm of Islamic thought practiced within these three cultural fields of the NU. Pesantren’s interpretation of Aswaja An-Nahdliyyah is thick, based on Bayani and Irfani. However, the scholars of NU and NGO activists are shifting in progress into Burhani’s epistemological model. In other words, methodologically they aspire to change in understanding Aswaja from qauli to manhaji, from Bayani-Irfani to Burhani, and from monolithic-dichotomic to integrative-progressive.